Efektivitas Penerapan Sanksi Denda E-Tilang Bagi Pelanggar Lalu Lintas Berdasarkan Undang-Undang Nomor 22 Tahun 2009 Tentang Lalu Lintas Dan Angkutan Jalan (Studi Di Polres Rembang) - Setiyanto Setiyanto; Gunarto Gunarto; Sri Endah Wahyuningsih (UNISSULA Semarang, 2017)
To achieve a relevant evidence of infringement (violation ticket) process its is necessary to have an information system that is supported by a network-based software or website that allows the dissemination of realtime information to every member of the police. The implementation of E-Tilang is could be an effective option to sanction the traffic offenders. Even tough the E-Tilang can not be said that it is effective because not every people in Indonesia are technologically literate. There are still many of them who do not know about the existence of E-Tilang so that they need for more vigorous and equitable socialization abaout it. Therefore this study intends to analyze the effectiveness of the implementation of Sanction of E-Tilang Penalty for Traffic Offenders Based on Law no. 22/2009 on Traffic and Road Transportation in the Territory of the Rembang Police, and to analyze how the implementation, constraints and the effectiveness of E-tilang system in the settlement of criminal cases of traffic violation in Rembang.E-Tilang has some advantages, it has faster service than a conventional one. This system is more practical and fast. The implementation of the electronic ticketing system (E-Tilang) is to facilitate speed and convenience, the openness of the execution of the ticketing process or as a substitute for on-site ticketing process. Some of the benefits for traffic violators in the presence of the E-Tilang system are the transparency of public apparatus's actions in government administration activities, community empowerment where people are expected to transmit the orderly attitude of the traffic after knowing the rules to those around them in order not to violate the existing regulations. The responsiveness of the authorities will be higher and more responsive to public complaints in traffic and equity, where violators with the same offense will get the same fine or penalty. Keywords: Effectiveness, Ticket ticket, E-Tilang, Traffic, Traffic Offense